ChocOmega-3: Innovative manufacturing of w-3-enriched chocolate - Pilavci, Esra; Baykara, Dilruba; Ozkan, Kubra; Tiryaki, Aysegul; Ayran, Melih Musa; Enguven, Gozde; Tut, Tufan Arslan; Bozdag, Mehmet Murat; Sagdic, Osman; Gunduz, Oguzhan; Narayan, Roger J.; Dogan, Canan (Accscience Publishing, 2024)
3D printing technology allows food to be shaped into unique and complex forms. Chocolate is frequently used in food printing due to its extrusion melting capacity and attractiveness. In this study, chocolates enriched with w-3 were produced with 3D printing technology. By using electrospraying, w-3 was encapsulated within sodium alginate (SA) microparticles, which were then used to coat 3D-printed chocolates. The w-3 blend and w-3-SA coated chocolates were compared. Before printing, the rheological properties of the chocolates were analyzed. In addition to their characteristics, the printed chocolates were evaluated for total phenolic content (TPC) and antioxidant capacity, in vitro gastrointestinal digestion, and w-3 release profile. Fourier transform infrared (FTIR) spectroscopy indicated that w-3 was successfully incorporated into the SA particles. According to mechanical testing, the chocolate structures coated with w-3-SA exhibited higher compressive strength than structures mixed with w-3. The results revealed that the incorporation of alginate into pure chocolate scaffolds through the coating process increased their compressive strength. The TPC and antioxidant capacities of w-3-SA microparticles (MP)-coated and w-3-mixed chocolate samples were also significantly increased compared to those of pure chocolate after in vitro digestion. The w-3-SA MP-coated chocolate reported a lower quality release profile.The faster release of encapsulated w-3 at a pH value of 7 may be attributed to the fact that SA particles dissolve faster in high pH environments. This study revealed that 3D printing technology could be actively leveraged to create food-based products with the necessary ingredients to meet consumer demand.
Keywords: 3D printing; Food technology; w-3; Electrospraying; Rheology; Bioaccessibility; POLYUNSATURATED FATTY-ACIDS; DARK CHOCOLATE; FISH-OIL; ANTIOXIDANT CAPACITY; MILK CHOCOLATE; OPTIMIZATION; PROTEIN; MICROENCAPSULATION; STABILIZATION; Engineering; Materials Science